IMPLEMENTASI PNPM MANDIRI PERDESAAN DI KECAMATAN TANON KABUPATEN SRAGEN TAHUN 2011 - Bambang Budi Legowo (JI@P, 2014)
This research is conducted to describe and to find some factors facilitatingand obstructing the implementation of National Program of Otonom RuralCommunity Empowerment (Program Nasional Pemberdayaan MasyarakatMandiri Perdesaan) in Tanon Sub District, Sragen regency in the year of2011. The program is intended to increase welfare and ability to find jobespecially for the poor. Fact shows, however, that the infrastructures are notmaintained by the program implementer, high amount of economic budget atthe sub district level is not made use. Theory advanced by Van Meter andVan Horn is applied in explaining the research problems. Descriptivequalitative method was used for describing in detail and depth the situationhappened in the field. Purposive sampling using snowball sampling was usedto select the respondents. Interactive analysis as suggested by Miles andHuberman was employed. To validate data, data triangulation method wasused. Based on research reslut, data show that the implementation of theprogram was run well, however, it needs more socialisation of the program,consistency of the program, and to inform the rural people more detail so thatpeople know the utilization of the program. Data also indicate that it isnecessary to increase local people training.Key words: National Program of Otonom Rural Community Empowerment;implementation.Pendahuluan